EFFICACY OF BRASSICA SORGHUM AND SUNFLOWER AQUEOUS EXTRACTS TO CONTROL WHEAT WEEDS UNDER RAINFED CONDITIONS OF POTHWAR, PAKISTAN - F. K. Awan; M. Rasheed; M. Ashraf; M. Y. Khurshid National Agricultural Research Centre; Islamabad (Journal of Animal and Plant Sciences, 2012)
Allelopathy is an environment friendly technique in controlling weeds and helpful in reducing cost of herbicide. An experiment was conducted at PMAS Arid Agriculture University during Rabi 2007, to observe the allelopathic effect of water extracts of sorghum, sunflower and brassica to control weeds in wheat using cultivar GA-2002. Extracts were prepared by taking chopped dry sorghum, sunflower and brassica herbage separately in water for one day in the proportion of 1:10 (w/v). The treatments were control, hand weeding, sorghum, sunflower and brassica individually and combined as sorghum+ sunflower, sorghum+ brassica, sunflower+ brassica and sorghum+ sunflower+ brassica. The experiment was laid out in Randomized Complete Block Design with four replications. Size of each individual plot was 5 × 6 m. Results indicated that the highest weed density and biomass suppression was achieved with hand weeding among all the treatments. Among the foliar application of extracts, the highest weed control was recorded with the combined application of concentrated aqueous extracts of sorghum, sunflower and brassica at 45 and 75 days after sowing followed by both sorghum+ sunflower. In case of growth and yield components, highest increase was recorded in manual weeding and lowest in case control.  Among extracts application treatments the highest increase in wheat biometry and yield attributes was found by combined application of sorghum, sunflower and brassica extracts compared to rest of the treatments.
Keywords: Allelopathy; sorghum; sunflower; brassica extracts; wheat (Triticum astivum L.); yield and weed control